Leaf margins in a deciduous lineage from the Greater Cape Floristic Region track climate in unexpected directions. Issue 5 (12th May 2020) - Frye, Henry A.; Mocko, Kerri; Moore, Timothy E.; Schlichting, Carl D.; Jones, Cynthia S.
Abstract : Premise: The functional significance of leaf margins has long been debated. In this study, we explore influences of climate, leaf lobing, woodiness, and shared evolutionary history on two leaf margin traits within the genus Pelargonium . Methods: Leaves from 454 populations of Pelargonium (161 species) were collected in the Greater Cape Floristic Region and scored for tooth presence/absence and degree of lobing. Tooth density (number of teeth per interior perimeter distance) was calculated for a subset of these. We compared five hypotheses to explain tooth presence and density using mixed effect models. Results: Tooth presence/absence was best predicted by the interaction of leaf lobing and mean annual temperature (MAT), but often in patterns opposite those previously reported: species were more likely to be toothed with warmer temperatures, particularly for unlobed and highly lobed leaves. In contrast, tooth density was best predicted by the interaction of MAT and the season of most rain; density declines with temperature as consistent with expectations, but only in winter‐rain dominated areas. Woody and nonwoody species within Pelargonium have similar associations between tooth presence/absence and MAT, contrary to the expectation that patterns within nonwoody species would be insignificant. Conclusions: We conclude Pelargonium leaf margins show predictable responses to climate, but these responses are complex and can contradict those found for global patterns across plant communities.